Penentuan Kelas Unggulan Berbasis Decision Support System Dengan Metode Simple Additive Weighting (Saw) - Zufria, Ilka; Hasugian, Abdul Halim; Simanjuntak, Salmah (LPPM UNIKA Santo Thomas Medan, 2020)
MTs 2 state Medan Jl. Administrator No. 3 Medan Estate Complex is one of the school governments engaged in education. With the rapid development of technology that develops with the development of science and technology, we must prepare human resources who are able to compete excellently. In order for the formation of quality students, the superior class is a gap in efforts to improve the quality of education in Indonesia. To get quality students will not be separated from good religious knowledge, because if students do not have religious knowledge it will cause competent children to do things that are deviant, whereas in the hadith it has been stated that morals are higher in the placement of knowledge, then a student who does not there are morals then their knowledge will be in vain. This study is to see that to enter the superior class with several specified criteria, namely: Al-Quran test, IQ test, medical history, parent's income, Sem-Odd Value, Sem-Even Value. If these criteria are met, a student will be selected through the results of the ranking of each criterion. Because it takes too much time and the limited ability to see all aspects at one time that has been determined accurately, it causes several errors in decision making. Therefore, a decision support system for selecting a superior class is needed with the criteria determined by the MTs state 2 Medan school, by using the simple additive weighting method (SAW) which can help the school to determine superior class students quickly and accurately. By using the SAW method formula that is connected with each existing criterion to produce a decision in selecting the superior class student.Â Keywords: superior class, decision support system, SAW